A novel process combining simultaneous partial nitrification, anammox and denitrification (SNAD) with denitrifying phosphorus removal (DPR) to treat sewage. (December 2016) - Wen, Xin; Zhou, Jian; Li, Yancheng; Qing, Xiaoxia; He, Qiang
Graphical abstract: Highlights: A novel SNAD-DPR process was established. Nitrogen and phosphorus could be simultaneously removed with lower aeration costs. Carbon source addition during start-up period had a huge impact on microbial community. Nitrosomonas, Candidatus brocadia and Thauera were dominant in SNAD system. Abstract: In this study, a novel process combined simultaneous partial nitrification, anammox and denitrification (SNAD) with denitrifying phosphorus removal (DPR) was proposed for advanced nitrogen removal. Firstly simulating sewage was introduced to a sequencing batch reactor (SBR) for organic matter removal and anaerobic phosphorus release (stage 1). Then effluent of stage 1 with low COD was discharged to a sequencing biofilm batch reactor (SBBR) for partial nitrification, anammox and partial denitrification (stage 2). The nitrate produced in SBBR was fed into SBR again, in which the nitrate was removed by DPR process (stage 3). The performance of the SNAD-DPR process was investigated. And effects of carbon source addition during start-up period on microbial community were discussed based on 16S rRNA amplicon pyrosequencing.